Progress on the Natural Products and Their Derivatives Containing Ureido Motif: Structure and Biological Activity - Zhang, Binbin; Jia, Yating; Yan, Jufen; Zhou, Jing; Rustamova, Nigora; Cao, Jianguo; Huang, Guozheng (Chemistry & biodiversity, 2025)
The ureido group, composed of two nitrogen atoms linked by a carbonyl moiety, serves as a crucial scaffold in pharmaceutical chemistry, enhancing biological activities such as anticancer and antimicrobial effects. This manuscript reviews studies published over the past two decades to underscore the significance of the ureido moiety in optimizing the therapeutic potential of natural products and their derivatives. Notable examples include tetrandrine, a bisbenzylisoquinoline alkaloid, whose ureido‐functionalized analogs demonstrate markedly improved anticancer activity against multidrug‐resistant tumors. Similarly, vinblastine derivatives incorporating ureido modifications have shown enhanced tubulin binding affinity and reduced systemic toxicity in preclinical models, addressing key limitations of the parent compound. In the antimicrobial domain, muraymycin analogs featuring ureido‐based structural tweaks exhibit superior antibacterial potency against Gram‐positive pathogens by strengthening interactions with bacterial membrane enzyme MraY. These case studies demonstrate how strategic ureido incorporation can overcome pharmacokinetic challenges while amplifying pharmacological efficacy. Such targeted modifications of natural product backbones offer a promising strategy for developing novel therapeutics, particularly in combating drug resistance and refining selectivity profiles. This review systematically evaluates structure–activity relationships and mechanistic insights to guide future ureido‐centric drug discovery efforts.